Fulgoromorpha (Hemiptera) records from Southwestern Turkey - Demir, Emine (ENTOMOLOGIA HELLENICA, 2018)
In the present study Fulgoromorph species collected from Gevne Valley and the surroundings located in southwest of Turkey were evaluated faunistically, ecologically and zoogeographically. In the surveys 43 species were identified to belong to 27 genera and 9 families. Herein, new records for the Mediterranean (4 species) and Central Anatolia (5 species) regions are reported. The species identified in the study area belong to 14 different zoogeographical elements of endemism and the endemism ratio of the area is 23.3%. Issidae is the most dominant family in the area since 74.0% of the specimens collected belong to this family.